Determinants of Adoption of Improved Varieties of Wheat (Triticum aestivum), Teff (Eragrostis teff), and Maize (Zea mays L.) in Central Ethiopia - Tekeste Kifle; Degefa Tolossa; Admasu Shibru; Dawit Alemu (Journal of Agricultural Extension, 2023)
This study determined factors of the adoption of improved varieties of certified maize, teff, and wheat seeds in central Ethiopia. The logit model was applied to estimate the likelihood of adoption decisions. The result showed that 29% of household respondents adopted improved seeds, while 71% relied on their local landraces. The findings also revealed that farmers' decisions to adopt wheat, teff, and maize varieties were significantly influenced by educational level, farm size, farming experience, income, credit access, extension contact, farm input, and distance to the market. Thus, the study recommends that the government should focus on strengthening extension services, improving access to improved seeds, expanding timely agricultural inputs supply, improving market opportunities, equipping knowledgeable farmers who increase the use of new varieties, and making the land more economical by sharing agronomic practices are areas that need policy attention enhancing the adoption of certified seeds of improved varieties.